PENGEMBANGAN MEDIA MOBIL-MOBILAN UNTUK MENERAPKAN PROFIL PELAJAR PANCASILA BERNALAR KRITIS DAN GOTONG ROYONG PESERTA DIDIK DI SEKOLAH DASAR - Fadilah, Hinda Aulia; Syarip Hidayat; Ahmad Mulyadiprana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to reveal and analyze the development of toy car media to implement the profile of Pancasila students with critical thinking and collaboration skills among elementary school students (a design research study in Grade IV at SDN 1 Margajaya). The method used is descriptive with a qualitative approach. Data collection was carried out through observation, interviews, and documentation. The technical analysis and data processing method used in this study is an interactive model. The final results of this study show that the project to strengthen the Pancasila student profile with the theme of sustainable lifestyle at SDN 1 Margajaya falls under the satisfactory criteria. In the critical thinking dimension, the target achievement reached 93.1%, with 12.3% of students showing development and 0.71% of students not yet developed. For the collaboration dimension, the target achievement reached 90.8%, with 12.15% of students showing development and 0.85% of students still not developed. The monitoring conducted by students regarding project achievements and the evaluation of the Pancasila student profile achievement is 94.2%.